Game Simulasi Menjahit âDRESSCODEâ Sebagai Bahan Pembelajaran Bagi Siswa SMK Tata Busana Berbasis Android - sukamto, sukamto; Sulistiyo, Wahyu; Lilavatie, Laresha (Teknik Elektro - Politeknik Negeri Semarang, 2016)
Educational game is the game designed to educate children or students in specific subject. There are a lot of educational systems which use the game for its media. Based on that issue, DRESSCODE try to create the mobile game application to help students learn about the design, pattern maker and sewing clothes in a fun way. This research tries to build a game rely on fashion by using Adobe Animate program. The goal of this project is to make student understand more and explore their creativity in fashion crafting through some elements such as fashion design, pattern cutting and clothes sewing. This research uses waterfall method in which the structure of the research is written ordinarily through analysis, design, code writing, and system examination. This game is suitable for 11th grade students of fashion majority in Vocational High School. The result of examination for this game based on the users satisfaction responses are 84,5% for children and 81,5% for teachers.